STUDI PENDAHULUAN KONDISI TERUMBU KARANG YANG MEMILIKI JARAK LOKASI BERBEDA DARI â€œFLARE PRODUKSIâ€ LAPANGAN MINYAK TIAKA - Mansyur, Kasim; Tisâ€™in, Musayyadah (FAPETKAN UNTAD, 2016)
The reseach aimed to evaluate the condition of coral reefs based onÂ location of coral reefs and production flare in Tiaka Oil Field and to evaluated parameter of water environmentÂ that effected by flare stack in Tiaka Oil field. The reseach used Line Interception Transect (LIT) metod at permanent transect and data of water biofisic, namely; (1) temperature (2) water transparency (3) current velocity, (4) salinity, (5) pH and (6) demand oxigen/DO by insitu. The data has been taken in September 2015, November 2015 and April 2016. The result of this research show that The Percentage of life hard coral cover at Tiaka Oil Field in station 1 is 52,56 %, station 2 is 73,58%, and stasiun 3, is 55,88%.Â Â Key words: Coral reefs, production flare, tiaka oil field